Sosialisasi Literasi Anti Korupsi Terhadap Siswa di Sekolah Menengah Pertama Negeri 32 Pekanbaru - Shentya Putri Serayu; Winda Nur Safitri Ritonga; Annastasya Amalia Putri; Hania Safitri Ramadhani; Puji Rahayu; M.Fathir; Adinda Mila Sari; Masayu Anas Tasya (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2024)
This service aims to create individuals who are not only educated about corruption but are also committed to fighting this practice for the sake of future generations of young people. This devition uses the method of implementing outreach and cultivating anti-corruption literacy in the environment of SMP Negeri 32 Pekanbaru. There are three stages of activity planning carried out, namely the first stage of preparation, which includes licensing, coordination and outreach with SMP Negeri 32 Pekanbaru. Second stage, implementation includes socialization and counseling. The third stage is evaluation and preparation of activity reports. The results of anti-corruption literacy socialization and counseling were carried out by conducting discussions and interviews regarding the understanding and application of Pancasila values ​​and how the concept of corruption in the context of Pancasila showed a positive impact on students' understanding of corruption with Pancasila values ​​so as to form an anti-corruption attitude and create an environment corruption-free school.